Indexing calcium score of the aortic valve to the annulus area improves the grading of aortic stenosis severity in patients within the grey zone of aortic valve calcification. (3rd October 2022) - Gomes, D; Reis Santos, R; Freitas, P; Presume, J; Mendes, G; Coutinho Santos, A; Guerreiro, S; Abecasis, J; Ribeiras, R; Andrade, M J; Campante Teles, R; Saraiva, C; et al.
Abstract: Introduction: Calcium score of the aortic valve (CaScAoV) is recommended as a supporting tool to assist in the grading of aortic stenosis (AS) severity when echocardiographic assessment is inconclusive. However, a significant proportion of patients have CaScAoV values within a "grey zone" between the "unlikely" and "likely" thresholds. The purpose of this study was to assess the potential usefulness of indexing CaScAoV to the area of the aortic annulus, in order to improve the discriminative power of CaScAoV in this subset of patients. Methods: Consecutive patients evaluated at a single center TAVI program were retrospectively identified and included in the analysis if cardiac CT and echocardiography were performed within a 6-month timeframe. Those with LVEF <50%, indexed stroke volume <35 ml/m 2, rheumatic heart disease, or bicuspid aortic valves were excluded. Severe AS was defined as mean transvalvular gradient ≥40 mmHg. The likelihood of severe AS assessed by CT was categorized according to the guideline-recommended sex-specific CaScAoV thresholds. Patients were considered to be in the "grey zone" if their CaScAoV values were between 800–1200 for women, and between 1600–2000 for men. Results: A total of 655 patients were included (282 men (43.1%), median age 83 years [IQR 79–86]). AS was considered severe by echocardiographic criteria in 587 patients (89.6%), and moderate in the remainder. Median transvalvular gradient was 49 mmHg (IQR 43–59), and median CaScAoV values were 3329 (IQR 2356–4500) for men, and 1995 (IQR 1462–2781) for women. Overall, 77 patients (11.7%) had CaScAoV values in the "grey zone", of which 24 (31.2%) had moderate AS (Figure 1). Patients within this region of uncertainty were no different form the others in terms of age, sex, annulus size and body surface area. In this subset of patients, indexing CaScAoV to aortic annulus area showed good discriminative power to identify severe AS (AUC 0.69, 95% CI 0.56–0.81, p=0.008). Using previously established thresholds (>300 AU/cm 2 for women and >500 AU/cm 2 for men), 48 patients (62.3%) were correctly reclassified (net reclassification index of 0.45, p=0.03). These findings were similar for both sexes. Conclusion: In patients undergoing cardiac CT for known or suspected severe AS with CaScAoV values within the "grey zone", indexing CaScAoV to the area of the aortic annulus improves the classification of AS severity and may decrease diagnostic uncertainty. Funding Acknowledgement: Type of funding sources: None.